Profil Kandungan dan Kelimpahan Mikroplastik pada Ikan Kakap Merah (Lutjanus sp.) yang Didaratkan di PPI Kedonganan, Bali - Gebi Gresi Martina Panjaitan; Ima Yudha Perwira; Ni Putu Putri Wijayanti (Current Trends in Aquatic Science, 2021)
This study aimed to determine the microplastic content and abundance on the stomach of Red Snapper (Lutjanus sp.) landed at Kedonganan Fishery Port (PPI), Bali. This study was conducted at The Kedonganan Fishery Port (PPI), Bali from November to December 2019. The fish samples used were: Lutjanus Malabaricus and Lutjanus Gibbus. The microplastic particles were extracted from the gut of the fish before analysis (type and amount of particles). The result showed that 77% of Red Snapper (Lutjanus sp.) landed at the PPI Kedonganan were contaminated by microplastics particles. The abundance of microplastics in Lutjanus malabaricus species was 7.86 particle/fish, while in the Lutjanus gibbus species was 4.46 particle/fish. The advances analysis showed that there were 3 types of microplastic particles found in this study: fragments (75 particles), film (45 particles), and fiber (65 particles).